2019
DOI: 10.1093/sleep/zsz125
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the use of screen electronic devices in the evening is associated with improved sleep and daytime vigilance in adolescents

Abstract: The use of screen electronic devices in the evening negatively affects sleep. Yet, sleep is known to be essential for brain maturation and a key factor for good academic performance, and thus is particularly critical during childhood and adolescence. Although previous studies reported associations between screen time and sleep impairment, their causal relationship in adolescents remains unclear. Using actigraphy and daily questionnaires in a large sample of students (12 to 19 years old), we assessed screen tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 57 publications
2
53
0
3
Order By: Relevance
“…In agreement with previous studies, the relationship between screen-time behaviors and physical activity is complex and not always consistent [55], which could be attributed to the implication of other uses of the smartphone and other related outcomes (e.g., sleep patterns or other sedentary behaviors) [56]. There are several studies suggesting that smartphone use at night is associated with altered sleep patterns [57,58] and sleep disturbances are associated with frequent smartphone use among adolescents [58].…”
Section: Discussionsupporting
confidence: 78%
“…In agreement with previous studies, the relationship between screen-time behaviors and physical activity is complex and not always consistent [55], which could be attributed to the implication of other uses of the smartphone and other related outcomes (e.g., sleep patterns or other sedentary behaviors) [56]. There are several studies suggesting that smartphone use at night is associated with altered sleep patterns [57,58] and sleep disturbances are associated with frequent smartphone use among adolescents [58].…”
Section: Discussionsupporting
confidence: 78%
“…In agreement with previous studies, the relationship between screen-time behaviors and physical activity is complex and not always consistent [79], which could be attributed to the implication of other uses of the smartphone and other related outcomes (e.g., sleep patterns or other sedentary behaviors) [80]. The identified research indicates screen time has affected sleep, mental and physical health in a particular population and exercise is beneficial for these variables.…”
Section: Physical Exercisessupporting
confidence: 79%
“…Two studies examined mobile phone use and daytime tiredness 35,53 . Redmayne et al (2013) found that children disturbed by their mobile phone at night at least once a week were 3.5 times more likely to experience daytime tiredness than children who were not disturbed by their mobile phone at night 53 Eleven studies investigated the relationship between electronic media use and delayed bedtime and sleep onset 23,24,40,43,45,46,[48][49][50][51]59 . Nine of these studies showed a positive association 23,40,43,45,46,48,49,51,59 .…”
Section: Daytime Tirednessmentioning
confidence: 99%